Prevalence of Untreated Canals and Their Association with Periapical Periodontitis Using Cone-beam Computed Tomography - Ebrahimi , Rayan; Khajeh, Samira; Paik, Hanieh; Moradi , Masoud; Khosravi , Mohammad Rastegar (Iranian Endodontic Journal, 2024)
Introduction: Untreated canals represent the primary cause of treatment failure in molars and the second leading cause in other dental groups. This study determined the prevalence of untreated canals and their relationship with periapical periodontitis using cone-beam computed tomography (CBCT) images. Materials and Methods: 385 CBCT images with at least one treated canal were selected from the oral and maxillofacial radiology center. The number of roots and canals, presence, and size of periapical pathology, and presence of untreated canals were recorded. The study used descriptive statistics and Chi-square, Fisher's exact, and odds ratio tests to analyze data. Results: Of the 2053 teeth examined, 14.9% had at least one untreated canal. Untreated canals in teeth increase the chance of having a periapical lesion, raising the prevalence by 11 times. Of these, 91.8% had both untreated canals and periapical lesions. This was more than teeth without untreated canals (35.8%). Most untreated canals were in maxillary molars (65.3%), and mandibular molars (12.54%). There was a statistically significant relationship (P<0.001) between the number of roots, canals, expansion, destruction, and jaw type with the prevalence of untreated canals. The maxillary first molar (68.66%) and second mesiobuccal (MB2) canal (63.27%) had the highest percentages of untreated canals. Conclusions: The MB2 had the highest prevalence of untreated canals. The presence of untreated canals significantly increased the risk of expansion and/or destruction. Therefore, identifying these conditions can also be useful in diagnosing untreated canals. Dentists should assess the anatomy of the tooth and the structure of the root canal to minimize the possibility of an untreated canal. CBCT can assist in this process.